Micro-learning with instructional content in the teaching of scientific research: A qualitative study conducted in Peru (LACCEI, 2024)
Micro-learning is a strategy used to improve student learning by using technological resources in a brief, specific and digital way. The objective was to understand and evaluate the use of micro-learning capsules in the development of the research course. The students, guided by the course teachers, elaborated learning microcapsules on scientific research topics. The time used was 8 minutes maximum and they were developed in the second unit of the course "thesis development". The microcapsules were reviewed and corrected. Subsequently, they were published in the Blackboard platform of the course to be shared. The "virtual discussion group" technique was used to explore the feelings of 10 key participants, who showed interest in the development of the strategy. The responses obtained were analyzed, and three subcategories emerged (a) socialization (b) type of learning and (c) emotions. The results showed that students learn or analyze better when they elaborate, research, propose and share content related to a selected topic